Control of Immune Response to Allogeneic Embryonic Stem Cells by CD3 Antibody–Mediated Operational Tolerance Induction. Issue 2 (22nd October 2015) - Calderon, D.; Prot, M.; You, S.; Marquet, C.; Bellamy, V.; Bruneval, P.; Valette, F.; de Almeida, P.; Wu, J. C.; Pucéat, M.; Menasché, P.; Chatenoud, L.
Abstract: Implantation of embryonic stem cells (ESCs) and their differentiated derivatives into allogeneic hosts triggers an immune response that represents a hurdle to clinical application. We established in autoimmunity and in transplantation that CD3 antibody therapy induces a state of immune tolerance. Promising results have been obtained with CD3 antibodies in the clinic. In this study, we tested whether this strategy can prolong the survival of undifferentiated ESCs and their differentiated derivatives in histoincompatible hosts. Recipients of either mouse ESC–derived embryoid bodies (EBs) or cardiac progenitors received a single short tolerogenic regimen of CD3 antibody. In immunocompetent mice, allogeneic EBs and cardiac progenitors were rejected within 20–25 days. Recipients treated with CD3 antibody showed long‐term survival of implanted cardiac progenitors or EBs. In due course, EBs became teratomas, the growth of which was self‐limited. Regulatory CD4 + FoxP3 + T cells and signaling through the PD1/PDL1 pathway played key roles in the CD3 antibody therapeutic effect. Gene profiling emphasized the importance of TGF‐β and the inhibitory T cell coreceptor Tim3 to the observed effect. These results demonstrate that CD3 antibody administered alone promotes prolonged survival of allogeneic ESC derivatives and thus could prove useful for enhancing cell engraftment in the absence of chronic immunosuppression.